Predictors of the COVID-19 Social Distancing Practice among Undergraduate Health Students in Samarinda City, Indonesia: A Cross-Sectional Study - Aspan, Siti Hadijah; Viwattanakulvanid, Pramon (Kesmas, 2021)
Social distancing is a health protocol recommended by the World Health Organization (WHO) for reducing the spread of COVID-19. Undergraduate health students play an important role in the dissemination of accurate information. This study identified predictors that influenced the COVID-19 social distancing practice and examined the sources of social distancing information among undergraduate health students in Samarinda City, Indonesia. This cross-sectionalonline survey study (March-April 2021) involved 422 undergraduate students from medicine, public health, and pharmacy faculties at Mulawarman University. Binary logistic regression was conducted to identify factors associated with the COVID-19 social distancing practice. The results showed that age (AOR =1.47; 95% CI = 1.97–2.22, p-value = 0.045), sex (AOR = 2.26; 95% CI = 1.38–3.69, p-value = 0.001), and attitude (AOR = 2.61; 95% CI = 1.75-3.90; p-va lue<0.001) was significantly associated with social distancing practices. The top three sources of COVID-19 social distancing information used were social media (80.6%), websites (14.0%), and television (3.8%). The study findings encourage the government to disseminate more health information on social media and education programs to this target population.